Multiple immediate implants placement with immediate loading - Sumit Narang; Anu Narang; Kapil Jain; Vineet Bhatia (Journal of Indian Society of Periodontology, 2014)
The replacement of missing teeth with implant-borne restorations has become a treatment modality accepted by the scientific community for fully and partially edentulous patients. Recent reports have demonstrated the successful placement of dental implants into the fresh extraction socket in the anterior as well as in molar regions, which is made possible due to modification in implant surface. The present case report highlights the placement of three bicortical screw (BCS) implants into the fresh extraction sockets and one  KOS implant in edentulous area with flapless technique. All the implants were immediately loaded and followed up for a period of 6 months.